The sadder but nicer effect: how incidental sadness reduces morally questionable behavior - Noval, Laura J. (Journal of business ethics, 2024)
This article explores the influence of sadness in ethical decision-making and behavior. In three laboratory studies, we found that an incidental state of sadness reduced individuals’ propensity to engage in morally questionable behavior, including both unethical and selfish acts (Studies 1 to 3). We found this effect to be mediated by the role of sadness in prompting people to pay more attention to the negative consequences of morally questionable acts and perceive those consequences as more problematic (Studies 2 and 3). This effect was consistent using different decision-making contexts and held when rewards to be gained from such behavior were relatively high. Several implications of these findings for business ethics and organizations are discussed.